1998
DOI: 10.1210/endo.139.4.5863
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor in Mouse Brain: Sex Differences and Similarities in Autoregulation1

Abstract: The androgen receptor (AR) is generally considered an autoregulated protein. However, studies in brain have produced mixed results regarding sex differences, which should be present given the higher endogenous levels of androgens in males, and the effects of gonadectomy, which presumably should lead to a loss of AR. Resolving these issues is a necessary step in developing a model of AR regulation in the central nervous system and, more broadly, in determining how regulation of this receptor may mediate neural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(25 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…In both immunohistochemistry and Western blotting, we detected that decreased AR-immunoreactivity in the amygdala and hippocampus of OCX rats, whereas AR-immunoreactivity were augmented in either DHTor T-treated OCX rats. The effects of androgen on AR-immunoreactivity in the amygdala or in hippocampus of male rats in our present study is similar to that reported previously in the in different brain regions including the hippocampus, preoptic area, hypothalamic and amygdaloid areas of young or adult rodents [14,20,62]. It has been known that among the amygdaloid nuclei the basolateral amygdala is primarily responsible for the association between the conditioned stimulus (dark compartment) and unconditional stimulus (foot shock) [63].…”
Section: Discussionsupporting
confidence: 90%
“…In both immunohistochemistry and Western blotting, we detected that decreased AR-immunoreactivity in the amygdala and hippocampus of OCX rats, whereas AR-immunoreactivity were augmented in either DHTor T-treated OCX rats. The effects of androgen on AR-immunoreactivity in the amygdala or in hippocampus of male rats in our present study is similar to that reported previously in the in different brain regions including the hippocampus, preoptic area, hypothalamic and amygdaloid areas of young or adult rodents [14,20,62]. It has been known that among the amygdaloid nuclei the basolateral amygdala is primarily responsible for the association between the conditioned stimulus (dark compartment) and unconditional stimulus (foot shock) [63].…”
Section: Discussionsupporting
confidence: 90%
“…Androgens exert their effects via the androgen receptor (AR), a ligand dependent nuclear transcription factor 52 that is highly regulated by circulating androgen levels 53,54 . Testosterone propionate administration to gonadectomised mice results in a significant linear trend in AR expression up regulation within various regions of both male and female brains 53 . PNA-treated female mice are hyperandrogenic and exhibit increased AR-positive cells within the AVPV, an important hypothalamic region for regulating female ovulatory cycles in rodent species 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen-treated male animals have been reported to show decreased levels of visceral fat with an increase in subcutaneous fat levels compared to control animals [22]. It has been shown that SAT has higher levels of ERs and progesterone receptors than androgen receptors (AR) in female animals [24]. One multicenter clinical study showed that cross-sex hormonal therapy in trans women and trans men resulted in a more female-like body fat distribution in trans women and vice versa in trans men, emphasizing the role of hormones in body fat distribution [25].…”
Section: Hormonal Factorsmentioning
confidence: 99%